3x-2x+5-1=4x+3-x-4

Simple and best practice solution for 3x-2x+5-1=4x+3-x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2x+5-1=4x+3-x-4 equation:


Simplifying
3x + -2x + 5 + -1 = 4x + 3 + -1x + -4

Reorder the terms:
5 + -1 + 3x + -2x = 4x + 3 + -1x + -4

Combine like terms: 5 + -1 = 4
4 + 3x + -2x = 4x + 3 + -1x + -4

Combine like terms: 3x + -2x = 1x
4 + 1x = 4x + 3 + -1x + -4

Reorder the terms:
4 + 1x = 3 + -4 + 4x + -1x

Combine like terms: 3 + -4 = -1
4 + 1x = -1 + 4x + -1x

Combine like terms: 4x + -1x = 3x
4 + 1x = -1 + 3x

Solving
4 + 1x = -1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
4 + 1x + -3x = -1 + 3x + -3x

Combine like terms: 1x + -3x = -2x
4 + -2x = -1 + 3x + -3x

Combine like terms: 3x + -3x = 0
4 + -2x = -1 + 0
4 + -2x = -1

Add '-4' to each side of the equation.
4 + -4 + -2x = -1 + -4

Combine like terms: 4 + -4 = 0
0 + -2x = -1 + -4
-2x = -1 + -4

Combine like terms: -1 + -4 = -5
-2x = -5

Divide each side by '-2'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| h(t)=-16t^2+64t+11 | | .85*(x+2)-x=0 | | -6(2x-6)+1=-12x+37 | | 10x-23=180 | | 23(x-7)=131 | | 5x^2+30-275= | | (2x+24)=x | | 3x^2-33x=0 | | (1+8x)(1+8x)=0 | | 5y-6+y+46=6y+40-2y | | -6x-7x=-52 | | 2(3+5x)-3=23 | | 6t^5+3t^4=-12t^3 | | 9x+5=9-(9x-3) | | 21x-28y+7=0 | | 49w^2-81g^2=0 | | e^9x+8=13 | | 81v^2-126v+49= | | 900x^2-1800x+900=0 | | x^2+14x+15= | | 4w^2+28wd+49d^2=0 | | t^2-3.2t-3.2=49 | | 40x^2+30x=0 | | 4r^2-36r+81=0 | | b^4-144=0 | | 5(9c^2-64)=0 | | 45c^2-32= | | -5x^3+4x^2=0 | | 3y^2+8y=12y+15 | | 7(x+1)-6x=-3 | | 5x-3=8x+12 | | 4x+2x-5=7 |

Equations solver categories